Search Frictions and the Liquidity of Large Blocks of Shares - Rui Albuquerque; Enrique Schroth (Tinbergen Institute, 2011)
This paper investigates empirically the illiquidity of majority blocks of shares in the context of a search model of block trades. The search model incorporates two aspects of illiquidity, or search frictions. First, upon a liquidity shock, the incumbent blockholders may be forced to sell to a less efficient buyer. Second, a block liquidity sale may occur at a fire sale price. We conduct a structural estimation of the model using data on majority block trades in the U.S. The structural estimation is particularly useful in this exercise as it allows us to evaluate the counterfactual price that would result absent liquidity shocks. Our results help shed light into the size of the marketability discount, the control discount and an illiquidity-spillover discount we identify, and on the determinants of aggregate liquidity.
Keywords: G34; 330; Block pricing; marketability discount; liquidity; control transactions; search frictions; structural estimation